An Ecofeminist Study of Anne Brontë’s The Tenant of Wildfell Hall (1848) - Muslim, Alaa Musadaq (Indian Journal of Information Sources and Services, 2025)
The Victorian novel The Tenant of Wildfell Hall (1848), which looks upon the movement from a certain environment by the main character, is investigated in this study. The female protagonist goes through various incidents with different female and male characters which ultimately forms her identity and way of thinking. This study argues by using ecocritical theories that nature or its absence can have a great effect on a person. Through using Lawrence Buell’s five-dimensional phenomenology the significance of place is analyzed in this book. This is followed by the application of the ecofeminist dualism theory of Val Plum Wood which reveals the relation between male and female characters and its development throughout the story. The aim of combining these two theories is to examine the effect a place has on the relationship between the two genders. The result of the analysis shows that female characters are mostly attached or long for rural environments, in contrast to male characters who adapt better in urban places. It is also concluded that the male characters change their attitude to women according to their place of habitat. While nature offers them a calmer mindset and better conduct, it is analyzed that the city makes them harsher in their personality.